2018
DOI: 10.1186/s41239-018-0123-0
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of gamification technique for higher education students engagement in polytechnic Muadzam Shah Pahang, Malaysia

Abstract: In recent years, gamification is becoming popular in education development to enrich students experience in classroom. However, there is still lack of awareness among educators and the concern of whether the gamification technique is acceptable by students. This paper presents the effectiveness of gamification technique to improve students' engagement in Database Design subject at Polytechnic Muadzam Shah Pahang, Malaysia. A framework to implement the gamification technique in higher education is also describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 16 publications
(37 reference statements)
5
64
0
5
Order By: Relevance
“…To remedy this problem, one of the most prominent instructional methods is through the gamification strategy. Researchers have acknowledged the values of gamification in influencing human behavior (Buckley & Doyle, 2016;Sailer & Homner, 2020), promoting engagement (Brophy, 2015;Rahman et al, 2018), generating motivation (Deterding et al, 2011;Hwang et al, 2015;Persico et al, 2019), promoting attractive competition (Huang et al, 2018), providing spontaneous immediate feedback (Bouchrika et al, 2019;Koivisto & Hamari, 2014), and enhancing students' learning achievement (Attali & Arieli-Attali, 2015;Buckley & Doyle, 2016;Yıldırım & Şen, 2019). Specifically, an enormous body of research has also indicated that game-based learning (GBL) instruction has significantly contributed to promoting students' language learning experience (Ataeifar et al, 2019;Klimova & Kacetl, 2018;Lee et al, 2016;Liu & Chu, 2010;Ma, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To remedy this problem, one of the most prominent instructional methods is through the gamification strategy. Researchers have acknowledged the values of gamification in influencing human behavior (Buckley & Doyle, 2016;Sailer & Homner, 2020), promoting engagement (Brophy, 2015;Rahman et al, 2018), generating motivation (Deterding et al, 2011;Hwang et al, 2015;Persico et al, 2019), promoting attractive competition (Huang et al, 2018), providing spontaneous immediate feedback (Bouchrika et al, 2019;Koivisto & Hamari, 2014), and enhancing students' learning achievement (Attali & Arieli-Attali, 2015;Buckley & Doyle, 2016;Yıldırım & Şen, 2019). Specifically, an enormous body of research has also indicated that game-based learning (GBL) instruction has significantly contributed to promoting students' language learning experience (Ataeifar et al, 2019;Klimova & Kacetl, 2018;Lee et al, 2016;Liu & Chu, 2010;Ma, 2017).…”
mentioning
confidence: 99%
“…Throughout recent years, many influential academics around the world have been interested in investigating Kahoot incorporated into a broad multidisciplinary context of the study (Esteves et al, 2017;Guardia et al, 2019;Ismail et al, 2019;Kinder & Kurz, 2018;Lee et al, 2019;Martins et al, 2019;Rahman et al, 2018). Those all works of literature agree that Kahoot can potentially facilitate pedagogical practices.…”
mentioning
confidence: 99%
“…In this study, the results showed that students in particular tended to engage in activities that were easier to use the platform than the benefits they could derive from the product. It was concluded that Perceived Ease of Use Items (PEOU) was a better indicator of the students' attitude toward gamification [30].…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire was validated by translationretranslation and applied on 20 students (The validity of the questionnaire was measured based on the content validity using the experts' views. Furthermore, the reliability of the questionnaire was confirmed using correlation coefficient of 0.74 [29,30]. Also we used E Game Flow qustionnire (scale to measure learners' enjoyment of e-learning games) [31].This questionnaire with 42 items in 5 continuum and 8 dimensions constructed .…”
Section: Modelmentioning
confidence: 99%
“…Recently, with the exponential growth of information and communication technology (ICT), mobile computing devices have become commonplace among university students [7,8]. Along with this trend, there also emerges a research interest in gamifying EE in recent years [9][10][11][12][13][14]. However, at present, it is not rare for university teachers to characterize mobile devices as detrimental to the quality of university education.…”
Section: Introductionmentioning
confidence: 99%